2006
DOI: 10.1093/carcin/bgl063
|View full text |Cite
|
Sign up to set email alerts
|

K-ras Asp12 mutant neither interacts with Raf, nor signals through Erk and is less tumorigenic than K-ras Val12

Abstract: Different mutant amino acids in the Ras proteins lead to distinct transforming capacities and different aggressiveness in human tumors. K-Ras Asp12 (K12D) is more prevalent in benign than in malignant human colorectal tumors, whereas K-Ras Val12 (K12V) associates with more advanced and metastatic carcinomas, higher recurrence and decreased survival. Here, we tested, in a nude mouse xenograft model, whether different human K-Ras oncogenes mutated at codon 12 to Val, Asp or Cys would confer NIH3T3 fibroblasts di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 46 publications
6
48
2
Order By: Relevance
“…In these cells, KRAS G12D interacts with RAF1 and initially leads to increased phosphorylation of ERK1/2. These results support our recent study showing that RAS-GTP in rat granulosa cells interacts with RAF1 directly (Wayne et al, 2007), as well as the studies of others who have shown that KRAS G12D selectively activates RAF1 and/or PI3K in a cell-and context-specific manner Cespedes et al, 2006;Gupta et al, 2007;Tuveson et al, 2004). However, KRAS G12D -mediated ERK1/2 phosphorylation is transient and becomes markedly reduced in the mutant granulosa cells in vivo and in culture.…”
Section: Research Articlesupporting
confidence: 92%
See 1 more Smart Citation
“…In these cells, KRAS G12D interacts with RAF1 and initially leads to increased phosphorylation of ERK1/2. These results support our recent study showing that RAS-GTP in rat granulosa cells interacts with RAF1 directly (Wayne et al, 2007), as well as the studies of others who have shown that KRAS G12D selectively activates RAF1 and/or PI3K in a cell-and context-specific manner Cespedes et al, 2006;Gupta et al, 2007;Tuveson et al, 2004). However, KRAS G12D -mediated ERK1/2 phosphorylation is transient and becomes markedly reduced in the mutant granulosa cells in vivo and in culture.…”
Section: Research Articlesupporting
confidence: 92%
“…Activation of small G-proteins within the RAS superfamily impact multiple downstream signaling cascades, including RAF1/MEK/ERK1/2 and PI3K/AKT/FOXO, in many tissues in a cell-and context-specific manner Cespedes et al, 2006;Gupta et al, 2007;Rocks et al, 2006). In response to growth-regulatory molecules, transient activation of RAS can stimulate controlled proliferation as well as differentiation of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Whether these are due to differences intrinsic to the host or a result of differences in the effects of different rAs mutations remains to be determined. several laboratories have demonstrated mutation-specific effects of different mutagenic rAs alleles on lung tumorigenesis in a variety of murine and cell culture models (26)(27)(28)(29)(30)(31)(32)(33)(34). on the other hand, the data of p53 and crM1 alterations after curcumin treatment in the present study cannot exclude the possible protective effects of curcumin at the molecular levels against lung tumor progression.…”
Section: Crm1 Expression In Bitransgenic Mouse Lung Tumor Modelcontrasting
confidence: 56%
“…Conflicting data exist with respect to the role of K-Ras in activating PI3K-AKT signaling. Some reports indicate that K-Ras activity does directly modulate AKT phosphorylation through stimulation of PI3K (60,62), whereas others have not found a direct stimulation of AKT activity by mutated and constitutively active K-Ras protein (35, 58, 63). …”
Section: Mol Cancer Res 2007;5(8) August 2007mentioning
confidence: 99%